2004
DOI: 10.1097/01.wcb.0000135592.28823.47
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Anti—Transferrin Receptor Antibody (OX26) and OX26-Conjugated Liposomes to Brain Capillary Endothelial Cells Using In Situ Perfusion

Abstract: Brain capillary endothelial cells (BCECs) express transferrin receptors. The uptake of a potential drug vector (OX26, or anti-transferrin receptor antibody IgG2a) conjugated to polyethyleneglycol-coated liposomes by BCECs was studied using in situ perfusion in 18-day-old rats in which the uptake of OX26 is almost twice as high as in the adult rat. Using radio-labeling, the uptake of OX26 by BCECs after 15-minute perfusion was approximately 16 times higher than that of nonimmune IgG2a (Ni-IgG2a). OX26 and OX26-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 45 publications
11
115
0
1
Order By: Relevance
“…However, our studies at a microscopic level rather indicated that the distribution of anti-TfR antibodies injected in the bloodstream was limited to BCECs. This is in agreement with the immunohistochemical work of Moos and colleagues, using anti-TfR antibody OX-26 in the rat brain (Moos and Morgan, 2001;Gosk et al, 2004). A previous electron microscopy-based report has also shown the accumulation of blood-borne horseradish peroxidase-labeled OX26 into BCECs, but the experiments in this study did not include controls (Broadwell et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, our studies at a microscopic level rather indicated that the distribution of anti-TfR antibodies injected in the bloodstream was limited to BCECs. This is in agreement with the immunohistochemical work of Moos and colleagues, using anti-TfR antibody OX-26 in the rat brain (Moos and Morgan, 2001;Gosk et al, 2004). A previous electron microscopy-based report has also shown the accumulation of blood-borne horseradish peroxidase-labeled OX26 into BCECs, but the experiments in this study did not include controls (Broadwell et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, most reports use indirect outcome measures such as protein expression or enzymatic activity to conclude on vector transport (Shi and Pardridge, 2000;Zhang et al, 2003b;Kumar et al, 2007). Studies systematically examining the brain penetration of OX-26 using radiolabeling and immunohistochemical approaches concluded that OX-26 is transported into BCECs, without actually crossing the BBB (Moos and Morgan, 2001;Gosk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vários sistemas nanoestruturados de carreamento de bioativos até o SNC já estão em estágios avançados de pesquisa, com resultados farmacocinéticos promissores, a saber: nanopartículas poliméricas 77 , nanoesferas poliméricas 78 , nanomicelas poliméricas 79 e lipossomas 80 .…”
Section: Sistemas De Liberação Controlada De Fármacosunclassified
“…Overall, encapsulation of a drug into liposomes may prolong drug circulation time in blood stream, reduce drug side effects, and enhance drug therapeutic effects in CNS. Indeed, liposomes were evaluated for CNS drug delivery in a number of publications [162,[167][168][169][170][171][172][173][174][175][176][177][178][179].…”
Section: Liposomesmentioning
confidence: 99%
“…Such immunoliposome constructs were used to deliver small drugs, Daunomycin [162], and Digoxin [182] as well as plasmid DNA [169] to the brain. Notably, OX26-conjugated liposomes selectively distributed to BMVEC but avoided choroid plexus epithelium, neurons, and glia [177]. (In related work OX26 antibodies directly linked to oligonucleotides [183] or fibroblast growth factor [172] enhanced delivery of these molecules to the brain.)…”
Section: Liposomesmentioning
confidence: 99%